Impact of Growing Up with a Chronically Ill Sibling on Well Siblings' Late Adolescent Functioning. (28th January 2013) - Fleary, Sasha A.; Heffer, Robert W.
Abstract : The purpose of this study was to explore the continuing impact of growing up with an ill sibling on well siblings' late adolescent functioning. Forty late adolescents (M age = 18.78, SD = 0.83 ), who identified themselves as growing up with an ill sibling, completed a semistructured interview, demographic questionnaire, Personality Assessment Screener, and My Feelings and Concerns Sibling Questionnaire. Participants reported clinically significant problems on some PAS scales, and gender differences were found for acting out and alienation. Significant relationships were reported for communication and social withdrawal and alienation. Both positive and negative themes about the experience were elicited from the responses in the semistructured interview. This study provides evidence for some lingering negative effects of growing up with an ill sibling on well siblings' late adolescent functioning. Additionally, evidence for siblings' development of positive characteristics that may act as protective variables as they face the stressors of late adolescence was also highlighted.